Waiting for the 7th wave of the pandemic: analysis of the COVID-19 cases from the ”Victor Babes” Hospital, Craiova - Lucian-Ion Giubelan; Florentina Dumitrescu; Iulian Diaconescu; Mircea-Catalin Fortofoiu; Cristina Ilie; Ilona Georgescu (Romanian Journal of Infectious Diseases, 2022)
COVID-19 is an ongoing pandemic and an analysis of the cases treated in ”Victor Babes” Hospital of Infectious Diseases and Pulmonology from Craiova. It has been performed between March 2020 and October 2022.